Adobe Photoshop Lightroom Classic CC classroom in a book 2018 release : the official training workbook from Adobe - Evans, John (Technical writer); Straub, Katrin (Classroom in a book., 2018)
Adobe Photoshop Lightroom Classic CC Classroom in a Book® New ways to assemble collections and more search filters make it easier than ever to organize your growing library and find the photos you need. Streamline your editing workflow using intelligent tools trained with thousands of professionally corrected images, and make more selective local adjustments with sophisticated color and tone range masking. Work on your photos on any device; then, create stylish books and print layouts, dynamic slideshows, and interactive web galleries to showcase your images-or publish them online with just a click. The fastest, easiest, most comprehensive way to learn Adobe Photoshop Lightroom Classic CC! Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program does-an official training series from Adobe, developed with the support of Adobe product experts. Adobe Photoshop Lightroom Classic CC Classroom in a Book (2018 release) contains 11 lessons that cover the basics and beyond, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. Purchase of this book includes valuable online features. Follow the instructions in the book's Getting Started section to unlock access to: " Downloadable lesson files you need to work through the projects in the book " Web Edition containing the complete text of the book, interactive quizzes, and videos that walk you through the lessons step by step, and updated material covering new feature releases from Adobe What you need to use this book: Adobe Photoshop Lightroom Classic CC (2018 release) software, for either Windows or macOS. (Software not included.) Note: Classroom in a Book does not replace the documentation, support, updates, or any other benefits of being a registered owner of Adobe Photoshop Lightroom Classic CC software